2008
DOI: 10.1073/pnas.0802127105
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in midbrain dopaminergic regulation of the human reward system

Abstract: The dopamine system, which plays a crucial role in reward processing, is particularly vulnerable to aging. Significant losses over a normal lifespan have been reported for dopamine receptors and transporters, but very little is known about the neurofunctional consequences of this age-related dopaminergic decline. In animals, a substantial body of data indicates that dopamine activity in the midbrain is tightly associated with reward processing. In humans, although indirect evidence from pharmacological and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
157
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(188 citation statements)
references
References 46 publications
(56 reference statements)
28
157
1
2
Order By: Relevance
“…This is in line with observations that older patients with schizophrenia require much less intensive maintenance antipsychotic treatment than their younger counterparts and could perhaps be explained by the fact that the dopamine system is age dependent, with significant reductions in dopaminergic transmission in older subjects being observed (Dreher et al 2008). The fact that the mean age in our study is 30.5 years could explain the negative finding.…”
Section: Heterogeneity Of Treatment Resistancesupporting
confidence: 92%
“…This is in line with observations that older patients with schizophrenia require much less intensive maintenance antipsychotic treatment than their younger counterparts and could perhaps be explained by the fact that the dopamine system is age dependent, with significant reductions in dopaminergic transmission in older subjects being observed (Dreher et al 2008). The fact that the mean age in our study is 30.5 years could explain the negative finding.…”
Section: Heterogeneity Of Treatment Resistancesupporting
confidence: 92%
“…This, along with reduced activity in this network during the Self and Other conditions, is in line with earlier reports of age differences in activation in reward related regions during tasks that directly tap into the learning and processing of the rewarding properties of stimuli (Dreher, et al, 2008;Mell, et al, 2009). However, the intrinsic functional connectivity of the RN was not reduced in older relative to younger adults, suggesting that age differences in this network are sensitive to task demands but not necessarily present in the basic underlying functional connections of these regions.…”
Section: Age Differences In Functional Connectivitysupporting
confidence: 91%
“…For example Dreher et al (2008) showed that older adults have less activity in the ventral striatum during reward anticipation, and a weaker relation between this activity and dopamine levels in the midbrain, relative to younger adults. Mell et al (2009) also reported an age reduction in striatal responses to learned reward.…”
Section: The Reward Network (Rn)mentioning
confidence: 99%
“…Several studies have shown that there are age reductions in striatal responses to learned reward 148 , and reward anticipation 149 . Only one study has directly examined the relation between functional activation during reward tasks and dopamine binding levels 150 . It showed that old adults not only have less activity in the ventral striatum during reward anticipation, they also show a weaker relationship between this activity and dopamine levels in the midbrain, relative to younger adults, suggesting that age-related dysfunction in this neurotransmitter system could impact multiple everyday decisions that rely on reward processing.…”
Section: Dopaminementioning
confidence: 99%